Strategies to Improve Emergency Nurses' Response Time Through Training Programs: Strategi untuk Meningkatkan Waktu Tanggap Perawat Gawat Darurat Melalui Program Pelatihan - Sari, Firdaus Indah; Purwaningsih, Purwaningsih; Qur’aniati, Nuzul (Indonesian Journal of Innovation Studies, 2024)
Background: Emergency units rely on nurses' rapid response times to manage critical situations effectively. Overcrowding and inadequate triage skills often compromise patient outcomes. Gap: Limited evidence exists on the most effective interventions to improve emergency nurses' response times. Aim: This systematic review evaluates evidence-based interventions for enhancing response times in emergency nurses. Results: From 15 studies, effective interventions include simulation-based education, triage training (e.g., Emergency Severity Index, Swiss Triage System), virtual simulations, and hands-on basic life support (BLS) training. BLS and triage training most significantly improve response times by prioritizing patient severity and enhancing emergency handling. Novelty: This review integrates global evidence, highlighting the combined impact of simulation-based and triage training programs. Implications: Healthcare systems should adopt tailored interventions, such as BLS simulations and triage training, to optimize emergency department efficiency and patient outcomes. Highlights: Critical Interventions: Simulation-based education and BLS training are the most effective in enhancing nurses' emergency response times. Global Evidence: Findings from 15 studies highlight diverse strategies, including virtual simulations and triage systems, for improving efficiency. Practical Implications: Tailored interventions like BLS and triage training directly improve patient outcomes and emergency department performance. Keywords: Nursing, Improve, Response Time, Emergency Rooms